The 20th century domestic water supply in Alor Setar, Kedah - Mohd Firdaus Abdullah; Arba’iyah Mohd Noor (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2019)
Alor Setar was the earliest location in Kedah which received the implementation of the domestic water supply plan by the British beginning in 1909. This initiative was due to administrative, economic, health, population and other relevant factors. Thus, the British built several water plants and the projects turned into a water supply module in other locations in the Kedah state. This paper would like to see the role of the British in developing the water supply system in Alor Setar from 1909 to 1957. This research began in 1909 due to the introduction to British advisers in the state of Kedah and ended in 1957 as the year was the final phase of the British domination in Kedah before the independence of the Federation of Malaya on August 31, 1957. This research employed materials and data from the National Archives of Kedah / Perlis, National Archives of Malaysia, University of Malaya Main Library, the Kedah Public Library, Tun Sri Lanang Library of Universiti Kebangsaan Malaysia and Kedah Water Company (SADA). The results of the study found that British advisers in Kedah successfully abandoned the water supply module in Alor Setar and succeeded in raising the standard of living of the residents at the stated locations.